IMPLEMENTASI KONSEP SEGITIGA S BERBASIS TRILOGI SANTRI DAN PANCA KESADARAN SANTRI DALAM MENINGKATKAN PIRAMIDA BELAJAR - Zakiyah BZ (Universitas Nurul Jadid Paiton Probolinggo, East Java, 2019)
The aim of this article is to describe how the implementation of the S triangle concept based on the Trilogy and Panca Kesadaran santri in improving the learning pyramid. This paper used qualitative methods with descriptive analysis. The results of this paper concluded that the implementation of the S triangular concept based on Trilogy and Panca Kesadaran santri in enhancing the learning pyramid has a positive effect on students through diversity lectures by adjusting the standard of competence in lesson plans by distinguishing learning methods and treatments in each different class. The concept of the S triangle based on the Trilogy and Panca Kesadaran santri in improving the learning pyramid emphasizes four intelligences which include spiritual intelligence, emotional intelligence, intellectual intelligence, and adversity intelligence called the learning pyramid. The concept of the S triangle is only as one stimulus in increasing intelligence with the Student Centered Learning (SCL) strategy that can be practiced in daily life through religious formation.